Book Reviews / Rezensionen - Eckhard Hein; Malcolm Sawyer; Engelbert Stockhammer; Joachim Becker; Mechthild Schrooten; Simon Sturn; Christian Spanberger (Intervention. European Journal of Economics and Economic Policies, 2011)
Books reviewed: G.C. Harcourt, Prue Kerr (2009): Joan Robinson, Basingstoke Tracy Mott (2010): Kalecki's Principle of Increasing Risk and Keynesian Economics, New York David Colander (ed.) (2006): Post Walrasian Macroeconomics. Beyond the Dynamic Stochastic General Equilibrium Model, Cambridge Pop-Eleches, Grigore (2009): From Economic Crisis to Reform. IMF Programs in Latin America and Eastern Europe, Princeton/Oxford Hans H. Bass, Toshihiko Hozumi, Uwe Staroske (Hg.) (2010): Labor Markets and Labor Market Policies between Globalization and World Economic Crisis. Japan and Germany, München Tim Jackson (2009): Prosperity Without Growth – Economics for a Finite Planet, London Walter O. Ötsch (2009): Mythos Markt. Marktradikale Propaganda und Ökonomische Theorie, Marburg
Keywords: 330